The contraceptive pill from the perspective of religion: observing the National Survey on Demographics and Health of Children and Women (PNDS-2006) (Research, Society and Development, 2021)
The present work aims to investigate whether there is any relationship between religion and decisions regarding the use of contraceptive methods, specifically the pill. For this purpose, we are based on the National Survey on Demography and Health of Children and Women (PNDS-2006). In some studies, religion did not influence the use of contraceptive methods, and the association between religion and the use of contraceptive methods was not significant, however, there is a higher prevalence of use of these methods by self-declared Catholic girls (80.9%) in relation to non-Catholic girls (70.3%). In others, we see the pill as the contraceptive method being the most remembered and sought after by women, in which the interference of religion in the use of contraception stands out and has not been captured in any of the national demographic and health surveys. Thus, in this work, we tested the hypotheses: 1) as null, that there is no interference in decisions regarding the use of contraceptive methods, specifically the pill; 2) as an alternative, that there is interference in decisions regarding the use of contraceptive methods, specifically the pill. We tested correlation and covariation using contingency tables, graphs, and pertinent significance tests – Pearson correlation, chi-square test, ANOVA trough Statistical Package for the Social Sciences. As a main result, the category “Religion” is not able to respond due to the influence on the use of contraceptive methods currently, as well as the search for the SUS or another institution to obtain the pill.